Self-deception - Fingarette, Herbert, 1921-2018 (Berkeley, Calif. : University of California Press, 2000)
Een herziene versie van zijn boek over zelfbedrog.
Originally published: London : Routledge & K. Paul ; New York : Humanities Press, 1969, in series: Studies in philosophical psychology. With a new ch.
Includes bibliographical references (p. 179-182) and index.
Keywords: Self-deception.